Prevalence of middle mesial canal in the Indian subpopulation of Greater Noida and the related variations in the canal anatomy of mandibular molars using cone-beam computed tomography - Sana Iqbal; Rohit Kochhar; Manju Kumari (Wolters Kluwer Medknow Publications, 2022)
Aim: Missed canals are one of the imperative reasons for failure of endodontic treatment of molars. This study aimed to determine the prevalence of middle mesial canal (MMC) in mandibular molars (1st and 2nd) in the population of Greater Noida and also to find relationship of intracanal distance between mesiobuccal (MB) and mesiolingual (ML) canals with the presence or absence of MMC. Materials and Methods: Previous cone-beam computed tomography (CBCT) scans of mandibular molars from patients were included. The following data were collected: Identification of MMC, the distance between MB and ML orifices, whether MMC was more prevalent in mandibular 1st or 2nd molar, whether MMC was prevalent in mandibular molars of right or left side. The results were analyzed using the Chi-square test and independent Student's t-test. Results: The overall prevalence of MMC was 21.8% (P < 0.05). MMC was more prevalent in mandibular first molar (29.7%) than mandibular second molar (16%) and overall prevalence of MMC was higher on the left side (24.3%) than on the right side (18.8%). The mean distance between MB and ML orifices was 2.9 mm and 3.4 mm with and without MMC respectively, (P < 0.05), i.e., the MB-ML intraorifice distance was inversely related with the presence of MMC. Binary logistic regression was used to determine the possible association between predictor (independent variable) the MB-ML orifice distance and the occurrence of the outcome variable, which was the presence of an MM canal. Conclusion: MMC is a common finding in the population of Greater Noida. Along with the use of CBCT, careful exploration of the pulpal floor between canal orifices is crucial to prevent missing the MMC.